CLAM FISHERY OF MULKY ESTUARY DURING 1978-1982 - Rao, G Syda (Indian Journal of Fisheries, 2011)
The magnitude of production of and effort spent in the clam fishery of Mulky estuary from 1978-79 to 1981-82 are presented. An estimated average of about 475 t of clams were landed annually, comprising Meretrix casta (76%) and Paphia malabarica (24%). M. casta is utilised for its meat and shells, whereas P. malabrica exclusively for its meat. The methods of fishing, utilisation and price structure are indicated. Heavy precipitation during S.W. monsoon appears to influence the clam fishery in the succeeding months